Management mess to leadership success 30 challenges to become the leader you would follow - Miller, Scott Jeffrey (Coral Gables Mango Publishing, 2019)
Scott Jeffrey Miller knows what it's like to fail. He was demoted fro his first leadership position after only three weeks -- and that's just one of several messy management experiences on his two-decade journey to leadership success. Scott's not alone. Everyone fails. But something sets Scott apart: his transparency and willingness to openly share his story in a way that is immediately relatable. In Management Mess to Leadership Success, you'll find 30 leadership challenges, honed by FranklinCovey through years of research that illustrate how to rise when you fall and how to survive and even thrive as an unfiltered leader. Illustrated with Scott Miller's real-life experiences, these challenges will teach you how to: lead difficult conversations and celebrate success; inspire trust, actively listen, and challenge paradigms; put the right people in the right roles; create a clear and actionable vision for your team; accomplish your organization's Wildly Important Goalsʼ; get the right results - in the right way; become the leader you would follow. Apply these 30 leadership challenges and change the way you lead yourself, lead others, and get results
Includes bibliographical references and index.
Keywords: Leadership